Farmed silver foxes (Vulpes vulpes): Preference for nest box roof may result from non-preference for an obstructed cage floor view - Mononen, Jaakko; Harri, Mikko; Rekilä, Teppo; Korhonen, Hannu T.; Niemelä, Paavo (fi, 1994)
Tutkimusraportti lisensiaattitutkielmassa v ok TUR